2013
DOI: 10.15193/zntj/2013/90/168-176
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Changes in Content of Nitrates (V) in Selected Spice Herbs Depending on Their Preservation Method and Storage Time

Abstract:  OCENA ZMIAN ZAWARTOŚCI AZOTANÓW(V) W WYBRANYCH ZIOŁACH PRZYPRAWOWYCH W ZALEŻNOŚCI OD SPOSOBU ICH UTRWALENIA I CZASU PRZECHOWYWANIAS t r e s z c z e n i e Celem pracy było określenie zawartości azotanów(V) w świeżych ziołach przyprawowych: bazylii pospolitej (Ocimum basilicum L.) odmiany 'Wala', cząbru ogrodowego (Satureja hortensis L.), bylicy estragon (Artemisia dracunculus L.), lubczyka ogrodowego (Levisticum officinale L.), lebiodki pospolitej (Origanum vulgare L.) oraz tymianku pospolitego (Thymus vulgar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Despite the low consumption of fresh aromatic herbs, most of these green leafy products accumulate high nitrate content in their tissues [42]. That high nitrate content in fresh tissue results is further increased nitrate concentration after drying and during storage [43]. Thus, given that they are mostly consumed as dry tissue, the implementation of cultivation practices that prevent nitrate accumulation would be widely acknowledged.…”
Section: Nutritional Compositionmentioning
confidence: 99%
“…Despite the low consumption of fresh aromatic herbs, most of these green leafy products accumulate high nitrate content in their tissues [42]. That high nitrate content in fresh tissue results is further increased nitrate concentration after drying and during storage [43]. Thus, given that they are mostly consumed as dry tissue, the implementation of cultivation practices that prevent nitrate accumulation would be widely acknowledged.…”
Section: Nutritional Compositionmentioning
confidence: 99%
“…An analysis of the interaction between the experimental factors revealed that the significantly highest amounts of nitrates were accumulated in lemon balm in the control treatment (2646 N-NO −3 kg −1 FM) and the lowest amounts were in summer savory treated with Maximus Amino Protect (1646 N-NO −3 kg −1 FM). Telesi ński et al [32] reported similar nitrate levels in summer savory (1700 N-NO −3 kg −1 FM).…”
Section: Factormentioning
confidence: 73%
“…Similar DM content was reported by Nurzyńska-Wierdak and Zawiślak [30] with 9.4% on average in sweet basil and lemon balm, Kazimierczak et al [13,31] with 22.1 to 26.0% in lemon balm, and Nurzyńska-Wierdak et al [15] with 13.5 to 17.4% in lemon balm and 11.9 to 17.1% in marjoram, depending on the sowing date and pot size. In a study by Telesiński et al [32], summer savory and marjoram had higher DM contents (21.4% and 30.3%, respectively).…”
Section: Resultsmentioning
confidence: 90%